DIFERENÇA ENTRE COLÁGENOS HIDROLISADOS DE NOVA TECNOLOGIA E VERISOL EM MARCAS DE EXPRESSÃO E NA QUALIDADE DA PELE EM TORNO DOS OLHOS. (CIPEEX, 2025)
Skin is the largest organ of the human body and performs various vital functions, including protection against external agents, regulation of body temperature, and sensory perception. As we age, our skin undergoes a series of changes that can be noticeable both visually and physically. One of the most evident changes is the appearance of wrinkles and fine lines, resulting from decreased skin elasticity and reduced production of collagen and elastin. Nutrition plays a key role in skin health, influencing its structure, function, and ability to defend against damage and diseases. However, it is unknown to what extent supplementation with different types of collagens can attenuate these effects in middle-aged women. Therefore, the present study aims to recruit 150 middle-aged women (35-58 years old) who will be randomized into three groups, Verisol Collagen 2.5 g/day, Peptech Collagen 2.5 g/day, and Peptech Collagen 10 g/day, 7 days a week, for 3 months. Skin hydration, oiliness, and flexibility, as well as the number and depth of expression lines, will be evaluated, along with plasma levels of Klotho, VEGF, and TGF-beta. Data will be analyzed, and graphs constructed using GraphPad Prism 5.0 software (California, USA). The normality distribution of the data will be assessed by the Kolmogorov-Smirnov test. Data with parametric distribution will be subjected to paired Student's t-test for intragroup comparison, and unpaired t-test will be used for comparison between groups. Significance levels will be considered statistically different for plt;0.05.
Keywords: skin health; collagen supplementation; growth factors